THE SHARED RESEARCH FACILITIES "GEOSPECTRUM" OF THE GEOLOGICAL INSTITUTE SB RAS - S. V. Kanakin; V. B. Khubanov; B. Zh. Zhalsaraev; V. F. Posokhov; B. V. Dampilova; E. A. Khromova; A. M. Khubanova; B. B. Lygdenova (Геодинамика и тектонофизика, 2022)
The Shared Research Facilities "Geospectrum" of the Geological Institute SB RAS (Ulan-Ude) was created based on the analytical base of the Geological Institute SB RAS (GIN SB RAS, Ulan-Ude). Its equipment is used for isotopy of light elements, U-Th-Pb geochronology of igneous, metamorphic and sedimentary rocks. In addition, a large volume of mineralogical and geochemical research is carried out to solve petrological, geochemical, lithological-geochemical and environmental basic and applied problems.